Application of Customer Relationship Management (CRM) Principles to Improve Customer Retention - Dony Ari Nugroho (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The application of Customer Relationship Management (CRM) principles is based on the company's need to face the challenges of increasingly fierce competition and evolving customer demands. The importance of maintaining a competitive advantage, companies need to manage relationships with customers effectively. CRM emerged as a strategic solution that allows companies to collect, analyze, and leverage customer data to improve their experience so that companies can not only better meet customer needs but also build sustainable loyalty. The purpose of this study is to explore the application of Customer Relationship Management (CRM) principles to improve customer retention. The research method used is a qualitative method with secondary data sources. The data collection technique used is documentation, then the data is analyzed with the Milles & Huberman approach through three stages, namely data reduction, data presentation and conclusion drawn. The results of the study show that the application of Customer Relationship Management (CRM) aims to increase customer retention through better and personalized relationship management. By leveraging customer data, CRM helps companies increase satisfaction, strengthen loyalty, and reduce churn. As a result, companies can improve business performance and profits.